Does school tracking affect equality of opportunity? New international evidence - Giorgio Brunello; Daniele Checchi (Institute for the Study of Labor (IZA), 2006)
This paper investigates whether at the interaction between family background and school tracking affects human capital accumulation. Our a priori view is that more tracking should reinforce the role of parental privilege, and thereby reduce equality of opportunity. Compared to the current literature, which focuses on early outcomes, such as test scores at 13 and 15, we look at later outcomes, including literacy, dropout rates, college enrolment, employability and earnings. While we do not confirm previous results that tracking reinforces family background effects on literacy, we do confirm our view when looking at educational attainment and labour market outcomes. When looking at early wages, we find that parental background effects are stronger when tracking starts earlier. We reconcile the apparently contrasting results on literacy, educational attainment and earnings by arguing that the signalling role of formal education captured by attainment matters more than actual skills measured by literacy in the early stages of labour market experience.
urn:nbn:de:101:1-2009062691
Keywords: 330; Schulauswahl; Bildungsinvestition; Gleichberechtigung; Theorie; Welt